2019
DOI: 10.3390/atmos10050282
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Based Designs to Mitigate Urban Heat: The Efficacy of Green Infrastructure Treatments in Portland, Oregon

Abstract: Urban heat is a growing environmental concern in cities around the world. The urban heat island effect, combined with warming effects of climate change, is likely to cause an increase in the frequency and intensity of extreme heat events. Alterations to the physical, built environment are a viable option for mitigating urban heat, yet few studies provide systematic guidance to practitioners for adapting diverse land uses. In this study, we examine the use of green infrastructure treatments to evaluate changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 68 publications
5
22
0
2
Order By: Relevance
“…This study has shown the interest of the complementary use of the latter two types of data, in particular LiDAR for a precise view of vegetation densities (high, medium, or low) but also remote sensing for surface temperature and water, humidity, and vegetation indices to a lesser extent. While we expected very satisfactory results with random forest modelling, confirming the results of previous studies [63,97,116], we were surprised to note also the very high performance of the classical multiple linear regression and PLS regression, with very low RMSE and often below 0.5 • C.…”
Section: Implication Of Important Predictors In Urban Air Temperaturesupporting
confidence: 89%
See 1 more Smart Citation
“…This study has shown the interest of the complementary use of the latter two types of data, in particular LiDAR for a precise view of vegetation densities (high, medium, or low) but also remote sensing for surface temperature and water, humidity, and vegetation indices to a lesser extent. While we expected very satisfactory results with random forest modelling, confirming the results of previous studies [63,97,116], we were surprised to note also the very high performance of the classical multiple linear regression and PLS regression, with very low RMSE and often below 0.5 • C.…”
Section: Implication Of Important Predictors In Urban Air Temperaturesupporting
confidence: 89%
“…This highlights the real need to use green and blue spaces solutions in order to limit the UHI and improve the thermal comfort. [97,116,139]…”
Section: Discussionmentioning
confidence: 99%
“…This can be done, for example, by increasing green vegetation in urban areas or by planting trees along roadsides in dry areas (e.g., [101]). However, as noted by [102], there is no one mitigation solution that fits all cases, and any mitigation must consider the specific characteristics of the specific geographic area.…”
mentioning
confidence: 99%
“…Therefore, the spatial identification of different levels of urban heat environment risk zone and the spatial-temporal change analysis of topological relationship among the risk zones will help to improve the scientific basis of green infrastructures spatial planning [45,46]. Efficient green infrastructure as nature-based solutions will be of great significance to mitigate the risk of urban heat environment and maintain the sustainable development of the city [47].…”
Section: Discussionmentioning
confidence: 99%